A comprehensive review of regional anesthesia for head and neck surgery. Issue 2 (2nd December 2021) - Muse, Iyabo O.; Straker, Tracey
Abstract : Head and neck surgery encompass a wide range of procedures from common tonsillectomy to major head and neck cancer resections requiring free flap reconstruction. Anesthetic management of these procedures relies predominately on general anesthesia; however, regional anesthetic techniques are available that can be used for both the primary anesthetic and analgesia, or in combination with general anesthesia. Traditionally most of these blocks were done blindly using anatomical structures, but with more availability of ultrasounds, these blocks are easier to perform, and with less complications. In this review, we will discuss the anatomical and ultrasound-guided approaches to regional anesthetic techniques that can be used in head and neck surgeries for primary intraoperative management, or in combination with general anesthesia for perioperative pain management. A discussion of outcomes studies of the different nerve blocks and potential complications associated with block placement will be highlighted.